Konsekuensi Hukum dari Pernikahan Dini serta Kaitannya dengan Kondisi Sosial di Desa Sukorejo - Bagus Arochman Felana; Diyan Putri Ayu; Wahyudi Wahyudi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The phenomenon of early marriage in Sukorejo Village is driven by parents' concerns about their children's behavior, readiness, efforts to reduce the family's economic burden, and low awareness of the importance of education. The implications of early marriage on family life include suboptimal child-rearing and education, as well as frequent conflicts that may lead to divorce. The community's views on early marriage fall into two categories: those who are opposed and those who support it. Those opposed argue that biological, sociological, and psychological immaturity can negatively impact the family life that is being built. Conversely, those who support early marriage believe it is a measure to preserve religious values and avoid free association and fornication. Additionally, some parents take pride in their daughters marrying early rather than becoming